Development of a synbiotic drinkable yogurt for school-aged children - Falke, Sarah (Kansas State University, 2015)
Fermented dairy products have long been associated with positive health benefits. Certain probiotics, such as Lactobacillus rhamnosus, have gained popularity as a natural way to improve health and immunity. Fermented dairy products are an easy way to incorporate and deliver probiotics to the consumer. Synbiotic systems are also being investigated as a method for promoting the growth and survival of probiotic bacteria, both during fermentation and after consumption. The purpose of this research was to develop a synbiotic yogurt drink, incorporating L. rhamnosus (probiotic) and inulin (prebiotic), and to investigate the effect of the synbiotic relationship on sensory, physical, chemical, and microbiological properties over time. Yogurt drinks containing the probiotic L. rhamnosus HN001 (treatment P), inulin (treatment I), and a synbiotic system (treatment S) were tested using a randomized block design. Color, viscosity, brix, syneresis, and pH were measured throughout a shelf-life of 28 days. Consumer acceptability was also tested with middle-school aged children. A shelf-life of 28 days at refrigerated temperature was found to be acceptable for the product based on chemical, physical, and microbial analysis. Based on sensory results, the synbiotic drink was found to be acceptable to the target consumers (scoring a 6.82 in “overall liking” on a 9-point hedonic scale), though the treatment with 3% inulin scored slightly higher in most categories (scoring a 7.24 in “overall liking” on a 9-point hedonic scale).
Keywords: Yogurt